Language as The Expression Representation of Thoughts - Anita Widjajanti (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
The focus of this research was ‘How is the form, content, and modes of language segment in the indicated media has many implicatures?’ The problem was studied by using a qualitative research design. The data were collected through observation, documentation, mingling, and focus group discussion. The data collected were analyzed by using the phenomenologist technique. The data fact “Everyone who commits obscene acts with other people of the same sex to person over 18 years old shall be convicted of the same criminal offenses if they use violence or threat of violence; violating public decency; publish; or contain pornographic elements”(note: the same sex, no violence or threat, no infringement,…., no pornography, is punished?) Language segment found in media was judged as (i) need to be reviewed, (ii) has pseudo certainty, (iii) open less satisfied opportunity, (iv) cause biased, and (v) lead injustice. Statements used in media that cause disgraceful behavior were not found. The modes of language use in media are intended to (i) give lessons, (ii) change behavior so that it does not violate the law, and (iii) fix reputation. Regarding the form, content, and mode formulated in media, it is suggested that statements must (i) be arranged in complete and flawless sentences, (ii) contain messages that cannot be refuted by anyone, and (iii) easily understood by anyone, not only law enforcers.